2021
DOI: 10.1016/j.jbc.2021.100307
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of trehalose recognition by the mycobacterial LpqY-SugABC transporter

Abstract: The Mycobacterium tuberculosis ( Mtb ) LpqY-SugABC ATP-binding cassette transporter is a recycling system that imports trehalose released during remodeling of the Mtb cell-envelope. As this process is essential for the virulence of the Mtb pathogen, it may represent an important target for tuberculosis drug and diagnostic development, but the transporter specificity and molecular determinants of substrate recognition ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 52 publications
(73 reference statements)
1
31
2
Order By: Relevance
“…Unlike the ligand-induced closed conformation upon trehalose binding seen in its homologs from other mycobacterial species (Liu et al, 2020;Furze et al, 2021), we observed a relatively open conformation in Mtb-LpqY. It is likely that trehalose recognition is primarily driven by selectivity that is accomplished by the spatial geometry of bindingsite residues through an extensive hydrogen-bonding network.…”
Section: The Mtb-lpqy-trehalose Complex Can Adopt An Open Liganded Formcontrasting
confidence: 67%
See 1 more Smart Citation
“…Unlike the ligand-induced closed conformation upon trehalose binding seen in its homologs from other mycobacterial species (Liu et al, 2020;Furze et al, 2021), we observed a relatively open conformation in Mtb-LpqY. It is likely that trehalose recognition is primarily driven by selectivity that is accomplished by the spatial geometry of bindingsite residues through an extensive hydrogen-bonding network.…”
Section: The Mtb-lpqy-trehalose Complex Can Adopt An Open Liganded Formcontrasting
confidence: 67%
“…SugA and SugB form a heterodimer that acts as a TMD and SugC acts as an NBD, which fuels transport using its ATPase activity (Sabharwal et al, 2020). LpqY, which is located in the periplasmic part, is an SBP of the SugABC transporter and shares $70% sequence identity with its nearest homologs from M. thermoresistibile and M. smegmatis, which have specificity for trehalose (Furze et al, 2021;Liu et al, 2020). In this study, crystal structures of M. tuberculosis LpqY (Mtb-LpqY) and of its complex with trehalose have been determined in order to understand the structural basis of its substrate specificity.…”
Section: Introductionmentioning
confidence: 99%
“…M. smegmatis is a non-pathogenic soil dwelling bacteria often used as a model organism for Mtb that has a significantly higher number of putative ABC-transporters for the import of carbohydrates compared to Mtb , 28 vs 4 respectively, which likely reflects the different environmental niches and lifestyles of these mycobacterial species ( Niederweis, 2008 , Braibant et al, 2000 ). A number of studies have found that each Mtb carbohydrate transporter is highly specific for a defined substrate ( Fenn et al, 2019 , Fullam et al, 2016 , Furze et al, 2021 ), and further experiments are now underway to investigate the role of UspABC in Mtb .…”
Section: Discussionmentioning
confidence: 99%
“…Recently our understanding of the role of the Mtb carbohydrate importers has improved and substrates for some of these systems have been identified ( Fenn et al, 2019 , Fullam et al, 2016 , Kalscheuer et al, 2010b , Parker et al, 2020 , Furze et al, 2021 , Lowery et al, 2015 ). Interestingly, it has been shown that the Mtb LpqY-SugABC transporter specifically recycles trehalose from the mycobacterial cell envelope and is essential for Mtb virulence ( Kalscheuer et al, 2010b , Furze et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation